The no-nonsense guide to archives and recordkeeping - Crockett, Margaret (Facet Publishing, 2016)
"This book is written for all those working in archives and records management, especially those without formal training, but also people managing archives and records management staff and those working closely with archives and records management, such as IT professionals, librarians and museum curators. It is intended as a practical how-to-do-it guide to managing archives and records and covers all aspects of recordkeeping and archives management following the records' journey through the lifecycle. Because of this, the chapters are not of equal length, but divide into the four main work areas: current records; records management; archives management; and archives preservation. The book deals with records and archives in all formats and unless specifically mentioned as paper or digital, the guidance is format-neutral. Reference to 'corporate' records is not intended in the narrow private enterprise sense, but rather the more general 'body corporate'. Similarly when 'business is mentioned, it is in the sense of the wider work and goals of any organization"--Introduction.